Success factors of E-assessment in computer science for higher education: perspectives from instructors - Alamr, Safiah Mohammed; Leon Urrutia, Manuel; Carr, Leslie Alan (Frontiers in Education, 2025)
Assessment is an essential element in higher education processes, and its use is becoming increasingly widespread with the digitalisation of universities. E-assessment plays a major role in the success of the educational process due to its benefits, such as improving students’ experience and performance and optimising instructors’ effort. This study aims to identify success factors for the use of e-assessment methods from instructors’ perspectives, focusing on computer science (CS) instructors who assess coding assignments in higher education in the UK and Saudi universities. A mixed-methods approach was employed, combining 16 interviews with CS instructors in the UK and Saudi universities and a survey as the quantitative element. Survey data revealed clear disparities in the perception of personalised feedback between the UK and Saudi Arabia. Findings indicate a lack of training courses for instructors and a shortage of specific automated tools for assessing coding. Few tools or systems are available for providing automated and personalised feedback, and existing e-assessment tools do not meet instructors’ expectations regarding flexibility, accessibility, scalability, practicality, validity, reliability, and authenticity. Instructors currently spend significant time and effort assessing coding assignments, which may hinder learning outcomes and the enhancement of educational activities. This thesis proposes a comprehensive framework outlining success factors for effective assessment, which can benefit e-assessment tool suppliers, instructors, and universities, ultimately enhancing the quality of instructors’ assessments.